Ukraine Education Policy Note : Introducing the New Ukrainian School in a Fiscally Sustainable Manner - World Bank (World Bank, Washington, DC, 2018)
The education sector in Ukraine is in the middle of ambitious - and long overdue - reforms that hold great promise to fundamentally transform the sector. New laws have been passed for higher education (in 2014), for research and scientific activity (in 2015), and, more recently, the framework law for the education sector, law on education (in 2017). Alongside the budget decentralization reform (2014) these laws represent a major shift towards devolving authority from central to local government and the expansion of decision-making autonomy by local authorities and education service providers (for example, schools and universities). Moreover, as part of these reforms, per student financing for schools was introduced in 2017, with the potential to incentivize local actors to use resources more efficiently. Taken together, these changes represent the most ambitious reform agenda for the education system since the collapse of the Soviet Union. However, the costliest feature of the general secondary education law is a promise to increase the starting salary of teachers to four times the minimum living wage by 2023. If not managed carefully, this increase threatens to put the sector on a fiscally unsustainable path which could undermine the broader reform agenda. This note highlights some areas of the reform agenda where more focus will be needed, and presents some options for how to implement the promised wage increase in a fiscally sustainable manner.